FREQUENCY OF MICROBIAL SPECTRUM OF SPONTANEOUS BACTERIAL PERITONITIS IN ESTABLISHED CIRRHOSIS LIVER - Zaman, Amjad; Kareem, Rahida; Mahmood, Rashid; Hameed, Khalid; Khan, Ejaz Muhammad (Journal of Ayub Medical College Abbottabad, 2011)
Background: Spontaneous bacterial peritonitis is one of the most frequent and serious complication in patients with liver cirrhosis and ascites associated with high mortality. Empiric antibiotic therapy should be initiated before the results of ascitic fluid cultures are available, guided by knowledge of the microbial spectrum of spontaneous bacterial peritonitis in a particular population. Methods: This is a descriptive study which was carried out in the Department of Gastroenterology and Hepatology, Postgraduate Medical Institute Hayatabad Medical Complex, Peshawar from January 2007 to December 2007. Fifty consecutive patients of established cirrhosis liver with ascites presenting with suspicion and or risk factors for spontaneous bacterial peritonitis were included in the study after informed consent. All selected patients were subjected to ascitic fluid tap. Twenty ml of ascitic fluid was aspirated in a heparinised disposable syringe; out of it 10 ml was immediately inoculated into blood culture bottle at bedside and sent for bacterial culture along with the remaining 10 ml for routine biochemical and cytological examination. Results: Out of 50 patients, 28 (56%) were diagnosed to have spontaneous bacterial peritonitis or its variants. Classic spontaneous bacterial peritonitis was present in 11 patients (39.28%), 16 (57.14%) patients were found to have culture negative neutrocytic ascites and one patient (3.57%) had bacterascites. Out of 28 cases of spontaneous bacterial peritonitis 12 samples of ascitic fluid showed positive culture reports. E. coli was the most frequently cultured organism isolated in 8 (66.66%) cases, Streptococcus pneumonae in 2 patients (16.66%), Staphylococcus aurus and Klebsiella each in 1 case (8.33%). Conclusion: Spontaneous bacterial peritonitis and its variants is a common complication of liver cirrhosis with ascites. E. coli is the most frequent offending organism in these cases. Knowledge of the microbial spectrum of spontaneous bacterial peritonitis in a particular population is important for the selection of the most appropriate empiric antibiotic regimen. Keywords: Cirrhosis liver, Spontaneous bacterial peritonitis, Ascitic fluid culture